Forensic computing - Sammes, A.J; Jenkinson, Brian 1950- (Springer-Verlag London Limited, 2007)
The second edition of this successful book shows how the contents of computer systems can be recovered for criminal evidence, even when hidden or subverted. Coverage includes Windows XP/2000 file systems, fast drives, new encryption technologies, and personal organisers